(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: There is still no consensus among ophthalmologists as to whether the prolonged use of topical bromfenac 0.09% is feasible in therapy for acute uveitis. Purpose: To improve the efficacy of treatment of HLA-B27-associated anterior uveitis through the use of Broksinak (containing bromfenac 0.09%) as an addditional therapy to the complex treatment regimen. Material and Methods: This study involved 42 patients (72 eyes) with a diagnosis of HLA-B27-associated anterior uveitis. Follow-up duration was 24 months. All patients were administered systemic methylprednisolone and methotrexate. Patients of the bromfenac group were administered Broksinak eye drops (containing bromfenac 0.09%) as an additional treatment to primary systemic therapy over the course of the follow-up. Patients of the control group were administered dexamethasone 0.1% eye drops. Results: There was no significant difference between the groups in terms of the number of recurrent uveitis episodes (р = 0.85) and laser flare reading during recurrent episodes (р = 0.56). In most recurrent uveitis episodes, laser flare readings were within the range of 20 to 50 ph/ms. There was a significant difference between the groups in the number of eyes that developed complications such as cataract (р = 0.05) and elevated intraocular pressure (р = 0.07). Cataract developed in 8 eyes of the bromfenac group and 19 eyes of the control group. At the final follow-up, elevated IOP was seen in 1 patient (1 eye) in the former group and 6 patients (7 eyes) in the latter group. At baseline, mean visual acuity (standard deviation (SD)) was 0.86 (0.21) for the bromfenac group and 0.78 (0.18) for the control group (p = 0.07). At the final follow-up, mean visual acuity (SD) was 0.86 (0.21) for the former group and 0.78 (0.18) for the latter group, ath the difference was significant (p = 0.006). No side effects from bromfenac 0.09% were noted in patients of the bromfenac group over the course of the study. Conclusion: The use of Broksinak containing bromfenac 0.09% as an additional therapy to complex treatment regimens improves the efficacy of treatment of HLA-B27-associated anterior uveitis. With the prolonged use of Broksinak, the bromfenac group exhibited a reduction in recurrence severity not less than the group treated with dexamethasone eye drops 0.1%. Moreover, the side effects (cataract and elevated IOP) typical for dexamethasone were seen significantly less frequently, and no corneal lesions were detected in the former group.